Differential Response of the Luteal Phase and Fertility in Cattle Following Ovulation of the First-Wave Follicle with Human Chorionic Gonadotropin or an Agonist of Gonadotropin-Releasing Hormone - Schmitt, É J.P.; Diaz, T.; Barros, C. M. [UNESP]; De La Sota, R. L.; Drost, M.; Fredriksson, E. W.; Staples, C. R.; Thorner, R.; Thatcher, W. W. (Oxford University Press (OUP), 1996)
A series of experiments with Holstein heifers was conducted to develop the capability of inducing accessory corpus luteum (CL) with a GnRH agonist (Buserelin, 8 μg; GnRHa) or hCG (3,000 IU) to increase plasma progesterone concentrations (Exp. 1, 2, and 3) and to test whether induction of accessory CL with hCG will increase conception rates in heifers (Exp. 4) and lactating cows (Exp. 5). In Exp. 1, heifers were treated on d 5 after estrus with GnRHa (n = 8) or saline (n = 7); heifers in Exp. 2 received hCG (n = 5) or saline (n = 4) on d 5. Experiment 3 allowed a contemporary evaluation of heifers treated on d 5 with GnRHa (n = 6), hCG (n = 6), saline (n = 6), or GnRHa at d 5 and hCG at the time of the induced ovulation (n = 5). The GnRHa and hCG were equally effective in inducing an accessory CL (93% induction rate), but the subsequent increase in progesterone concentrations was greater in hCG-treated heifers. A greater half life of hCG may provide longer LH-like stimulation of the first-wave follicle and subsequent developing accessory CL or a greater luteotropic effect on the original CL. Induction of an accessory CL with hCG on d 5 or 6 after insemination did not increase pregnancy rates in fertile heifers (Exp. 4: hCG = 64.8% vs control = 62.9%; n = 243) or lactating dairy cows during summer heat stress (Exp. 5: hCG = 24.2% vs control = 23.5%; n = 201).
Keywords: Corpus Luteum; Fertility; Follicles; GnRH Agonist; hCG; Progesterone